Rancang Bangun Pesawat Elektrokardiogram (EKG) Melalui Liquid Crystal Display Berbasis Arduino UNO - Erliwati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
This study aims to make an Electrocardiogram (ECG) aircraft module through an Arduino Uno-based Liquid Crystal Display and determine the level of accuracy and error of the tool made. In general, the main function of the heart is to pump blood throughout the body and accommodate it again after cleaning the lungs. This means that the function of the human heart is as a means or organ for pumping blood in humans. At that time the heart provides sufficient blood oxygen and flows throughout the body, and cleanses the body of metabolic products (carbon dioxide). In the heart, oxygen-rich blood coming from the lungs is pumped to the tissues throughout the human body. The heart is an organ consisting of muscles. The way it works resembles smooth muscle, which is beyond our will (influenced by the autonomic nervous system). After carrying out the process of making tools, writing scientific papers from literature studies, planning, experiments to data collection and data analysis, several conclusions can be drawn as follows, modules in the design and construction of variable power supplies and ECG devices can be designed and used, The results of testing and measuring heart rate on the module can be utilized, meaning that the results of measuring heart rate are accurate.